2018
DOI: 10.1186/s12943-018-0913-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tumor metabolic microenvironment on regulatory T cells

Abstract: Recent studies have shown that on one hand, tumors need to obtain a sufficient energy supply, and on the other hand they must evade the body’s immune surveillance. Because of their metabolic reprogramming characteristics, tumors can modify the physicochemical properties of the microenvironment, which in turn affects the biological characteristics of the cells infiltrating them. Regulatory T cells (Tregs) are a subset of T cells that regulate immune responses in the body. They exist in large quantities in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 137 publications
0
94
0
1
Order By: Relevance
“…As the gene with the highest mutation rate in PTC, the BRAF gene is of great significance for the development of PTC and is widely used in clinical practice. Testing for the BRAF V600E mutation is important, as this mutation is involved in the following: early diagnosis of thyroid cancer with FNC, independent risk factor prediction of PTC high-risk age, independent risk factor prediction of PTC lymph node vascular invasion and lymph node metastasis, prognosis evaluation of PTC, and posttreatment management [64][65][66][67][68][69][70]. The results of this study suggest that BRAF mutations should be used as an important indicator when developing individualized treatment options for patients with PTC.…”
Section: Discussionmentioning
confidence: 89%
“…As the gene with the highest mutation rate in PTC, the BRAF gene is of great significance for the development of PTC and is widely used in clinical practice. Testing for the BRAF V600E mutation is important, as this mutation is involved in the following: early diagnosis of thyroid cancer with FNC, independent risk factor prediction of PTC high-risk age, independent risk factor prediction of PTC lymph node vascular invasion and lymph node metastasis, prognosis evaluation of PTC, and posttreatment management [64][65][66][67][68][69][70]. The results of this study suggest that BRAF mutations should be used as an important indicator when developing individualized treatment options for patients with PTC.…”
Section: Discussionmentioning
confidence: 89%
“…The hypomethylation-upregulated genes were enriched in biological processes of cell migration and proliferation. GO cell component analysis showed that the upregulated genes were significantly enriched in the extracellular exosome, focal adhesion, endoplasmic reticulum, cell surface [38][39][40][41][42]. Besides, for molecular function, the hypomethylationupregulated genes were significantly enriched in calcium ion binding, GTP binding, extracellular matrix structural constituent, GTPase activator activity [43].…”
Section: Discussionmentioning
confidence: 99%
“…Sustained angiogenesis is a key element in tumorigenesis. In an anoxic environment inside a tumor mass, hypoxia-inducible factor-1 (HIF-1) induces the expression of genes involved in angiogenesis [100][101][102]. HIF-1α is a crucial oxygen sensor and plays a leading role in angiogenesis.…”
Section: Pvt1 Participates In the Downstream Angiogenesis-related Sigmentioning
confidence: 99%